Prevalence of depression and its associated factors among the doctors working in a private medical college, Trichy- a cross sectional study - Ponnan, Sathasivam; Mareeswaran, N.; ., Thalha; Tamizhan, T. (International Journal Of Community Medicine And Public Health, 2020)
Background: Stress is one among the leading health problem throughout the world. Stress due to family problems and work related are often encountered. Among the various professionals, health care providers are found to be more depressed than others. This study was conducted with an objective to study the socio demographic characters of the study participants, to study the depression status of the study participants and to study the association between various factors and depression. Methods: This descriptive cross sectional study done among the doctors working in a tertiary teaching hospital. A total of 150 participants were included in this study. Simple random sampling method was used to identify the study participants. Results: Around 76% of the participants belongs to the age group of 20-30 years of age. 71.3% of the study population were junior residents. Nearly 64% were found to be depressed among which 8% were found to be on severely depressed. Statistical significant association was found between factors like designation and time spending with family with depression. Conclusions: Since stress and burnout became the leading mental health problems, and health care providers posing as a vulnerable group by virtue of their profession. Hence behavioral therapy sessions and stress management programs are to be conducted frequently to screen as well to relieve from the mental health issues.